Cooperative Integrated Reading Composition to improve pupils’ reading comprehension achievement and motivation - Hayatina, Maulida; Fajrina, Salina Ahdia (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The focus of the study was to determine the effect of Cooperative Integrated Reading Composition (CIRC) to improve pupils’ reading comprehension achievement and motivation. A quantitative approach with a quasi-experimental design was used for this study. Interviews were also used to support the quantitative data. A total of 54 fifth grade pupils from the district of Kalimantan, Banjar, Indonesia were involved in the study. There were 28 pupils in the experimental group and 26 pupils in the control group. Quantitative data were collected from the pre and posttests and surveys, while the qualitative data came from the interviews. The quantitative data were analyzed by using descriptive and inferential analyses. Descriptive analysis showed the frequencies, means, and standard deviation, while the inferential statistics involved an independent t-test. The findings of the pre and posttests showed that there was a significant improvement in achievement for the experimental group (M=91.96, SD=5.33) when compared to the control group (M=85.38, SD=5.28), t(52)=4.55, p